1989
DOI: 10.1177/001698628903300303
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Procedures Used for Identifying Gifted Learning Disabled Children

Abstract: Since the early 1970s, concern for children who are both gifted and handicapped has risen dramatically. Books written about this emerging field deal with identification and programmatic concerns (e.g., Fox, Brody, and Tobin, 1983) and also with case studies illustrating the ways in which the two conditions may coexist (Whitmore and Maker, 1985). This research focuses on the problems involved in identifying the child who is both gifted and learning disabled (GLD). The state of the art is demonstrated by surveyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 10 publications
(11 reference statements)
1
17
0
Order By: Relevance
“…Although most of the teachers had little knowledge or training in the area of learning disabilities, results from this research revealed that teachers of gifted students were "less inclined to refer learning disabled and poor children than identically described children without those particular traits" (p. 37). The author noted that this research supported similar findings from a former study (Boodoo et al, 1989) indicating that general classroom teachers are also less inclined to refer such students for possible placement in gifted programs. Such attitudes leave entire segments of school populations unserved by appropriately challenging programs.…”
Section: Evidence Of Abilities: a Summary Of Researchsupporting
confidence: 84%
“…Although most of the teachers had little knowledge or training in the area of learning disabilities, results from this research revealed that teachers of gifted students were "less inclined to refer learning disabled and poor children than identically described children without those particular traits" (p. 37). The author noted that this research supported similar findings from a former study (Boodoo et al, 1989) indicating that general classroom teachers are also less inclined to refer such students for possible placement in gifted programs. Such attitudes leave entire segments of school populations unserved by appropriately challenging programs.…”
Section: Evidence Of Abilities: a Summary Of Researchsupporting
confidence: 84%
“…(Som, 1996), to screening methods (Wilson and Reichmuth, 1985), both in finding subjects with learning difficulties and those with high abilities (Satz and Fletcher, 1988;Boodoo et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…In general, though, they are underrepresented in gifted programs. For example, Boodoo et al (1989) surveyed Special Education teachers and directors of gifted programs in Texas and found that teachers and schools did not deal well with identifying and therefore providing for gifted learning disabled students. At the time Boodoo et al (1989) undertook this research, programs for gifted students were not mandated in Texas.…”
mentioning
confidence: 99%
“…For example, Boodoo et al (1989) surveyed Special Education teachers and directors of gifted programs in Texas and found that teachers and schools did not deal well with identifying and therefore providing for gifted learning disabled students. At the time Boodoo et al (1989) undertook this research, programs for gifted students were not mandated in Texas. Mandating did not occur until later in 1990 and made little difference to the number of gifted learning disabled students participating in programs for the gifted in Texas.…”
mentioning
confidence: 99%
See 1 more Smart Citation